Prevalence of viral gastroenteritis in children with acute gastroenteritis in Babol, Iran - Savadkoohi, Rahim Barari; Ahmadpour-Kacho, Mousa; Yahyapour, Yousef (Journal of Pediatric Infectious Diseases, 2007)
Viral gastroenteritis is considered a significant cause of death and is a common cause of hospitalization worldwide. This study was performed to assess the role of rota, adeno and astrovirus in children with acute diarrhea in one main children's hospital in Amirkola, Babol North of Iran. In this cross-sectional study, stool specimens from 208 children suffering from acute diarrhea referred to Amirkola children's hospital were tested for the presence of rota, adeno and astrovirus by a monoclonal antibody-based enzyme immunoassay. Demographic data were gathered by a questionnaire. The prevalence of viral causes of acute gastroenteritis was reported by relative frequency. Rota, adeno and astrovirus antigens were detected in 61.1%, 2.9% and 2.4% of patients respectively. Infants between 6 and 12 months of age were most frequently affected by rotavirus (29.8%) (P < 0.03). Rotavirus infection was significantly less frequent in summer and spring than winter and autumn (P < 0.0001). No significant difference was observed in rotavirus infection between male and female but the prevalence of adenovirus in girls was significantly higher than boys (P < 0.05). Rotavirus can be regarded as a major etiologic agent of acute diarrhea in children less than two years old at Amirkola children's hospital, Babol. Immunization may protect the children before their first symptomatic infection.
Keywords: Gastroenteritis; children; ELISA; rotavirus; adenovirus; astrovirus